2016
DOI: 10.1016/j.celrep.2016.07.044
|View full text |Cite
|
Sign up to set email alerts
|

Genetic Disruption of Arc/Arg3.1 in Mice Causes Alterations in Dopamine and Neurobehavioral Phenotypes Related to Schizophrenia

Abstract: Summary Human genetic studies have recently suggested that the postsynaptic Activity-regulated cytoskeleton-associated protein (Arc) complex is a convergence signal for several genes implicated in schizophrenia. However, the functional significance of Arc in schizophrenia-related neurobehavioral phenotypes and brain circuits is unclear. Here we find that, consistent with schizophrenia-related phenotypes, disruption of Arc in mice produces deficits in sensorimotor gating, cognitive functions, social behaviors, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

10
128
4

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 95 publications
(142 citation statements)
references
References 74 publications
10
128
4
Order By: Relevance
“…Our observations here reveal reliable anxiolytic-like effects in Arc KO mice across three different behavioral tests While previous reports using the same strain of Arc KO mice have noted significant decreases 60 and increases 58 in locomotion, we observe no significant differences in Arc KO mouse activity in a locomotor assay (Fig. 1 d-f).…”
Section: Discussionsupporting
confidence: 60%
“…Our observations here reveal reliable anxiolytic-like effects in Arc KO mice across three different behavioral tests While previous reports using the same strain of Arc KO mice have noted significant decreases 60 and increases 58 in locomotion, we observe no significant differences in Arc KO mouse activity in a locomotor assay (Fig. 1 d-f).…”
Section: Discussionsupporting
confidence: 60%
“…Chronic cranial windows are broadly used to study the morphology of neurons (Fu et al, 2012; Holtmaat et al, 2009; Mastwal et al, 2014; Yang et al, 2010), to examine gene expression patterns in individual neurons (Cao et al, 2015; Wang et al, 2006), for photo-stimulation through optogenetic methods (Carrillo-Reid et al, 2016; Silasi et al, 2013), and to image neural activity through genetically encoded calcium indicators such as GCaMP (Andrew et al, 2014; Chen et al, 2013; Manago et al, 2016). However, due to inflammation and tissue regrowth after surgery, success rates of clear windows vary and tend to be low (Holtmaat et al, 2009; Yang et al, 2010).…”
Section: Discussionmentioning
confidence: 99%
“…In addition to schizophrenia-related behavioral phenotypes, we found that genetic disruption of Arc in mice reduces frontal dopamine release (Managò et al, 2016). In further support of this finding, two-photon imaging of genetically encoded calcium indicators in the frontal cortex revealed that VTA stimulation-evoked activity is significantly reduced in Arc mutant mice in comparison to wild-type mice (Figure 2B).…”
Section: Genetic Disruption Of Arc Causes Alterations In the Dopaminementioning
confidence: 99%
“…The slower processes in the hierarchy integrate the faster dynamics and reach threshold for activation gradually. But once activated, the effects of slower processes persist longer and modulate the amplitude of the faster dynamics (Figures are modified with permission from Mastwal et al, 2014; Managò et al, 2016; Ye et al, 2016). …”
Section: Dopamine Is Required For the Amplification Of Activity-depenmentioning
confidence: 99%
See 1 more Smart Citation